Gambaran Tingkat Pengetahuan Ibu Tentang MP-ASI Usia 6-12 Bulan Di Desa Pakahan, Jogonalan, Klaten - Anna Uswatun; Lilik hartati (INVOLUSI: Jurnal Ilmu Kebidanan, 2020)
Improper feeding practices are a cause of nutritional problems in infants and toddlers. In order to support complementary foods related to infant growth or reduce nutritional deficiencies in infants, support for complementary foods with age-appropriate supplementary feeding. Improper complementary feeding practices can be affected by the level of knowledge. This study aims to determine the knowledge of mothers about complementary breastfeeding aged 6-12 months in Pakahan Village, Jogonalan, Klaten. This research method is descriptive with cross sectional design. The number of research samples were 34 respondents. Sampling with total sampling technique. The instrument used was a questionnaire. Data were analyzed using the univariate test in the form of a percentage. The results showed that the respondents in this study had characteristics, namely most of them were aged 20-35 years (64.7%), had a high school / vocational education (58.8%) and were housewives (82.4%). Maternal knowledge about complementary breastfeeding aged 6-12 months is good, namely 31 people (91.2%). The conclusion of this study is that the knowledge of mothers about complementary breastfeeding aged 6-12 months in the village of Pakahan Jogonalan Klaten is good. Midwives must improve service standards and provide health education about complementary ASI aged 6-12 months for mothers to improve proper and proper feeding patterns.